Controlled Ovarian Stimulation Using Medroxyprogesterone Acetate and hMG in Patients With Polycystic Ovary Syndrome Treated for IVF: A Double-Blind Randomized Crossover Clinical Trial. Issue 9 (March 2016) - Wang, Yun; Chen, Qiuju; Wang, NingLing; Chen, Hong; Lyu, Qifeng; Kuang, Yanping
Abstract : Abstract: Ovarian hyperstimulation syndrome (OHSS) during ovarian stimulation is a current challenge for patients with polycystic ovarian syndrome (PCOS). Our previous studies indicated that progestin can prevent premature luteinizing hormone (LH) surge or moderate/severe OHSS in the general subfertile population, both in the follicular-phase and luteal-phase ovarian stimulation but it is unclear if this is true for patients with PCOS. The aim of the article was to analyze cycle characteristics and endocrinological profiles using human menopausal gonadotropin (hMG) in combination with medroxyprogesterone acetate (MPA) for PCOS patients who are undergoing IVF/intracytoplasmic sperm injection (ICSI) treatments and investigate the subsequently pregnancy outcomes of frozen embryo transfer (FET). In the randomized prospective controlled study, 120 PCOS patients undergoing IVF/ICSI were recruited and randomly classified into 2 groups according to the ovarian stimulation protocols: hMG and MPA (group A, n = 60) or short protocol (group B, n = 60). In the study group, hMG (150–225IU) and MPA (10 mg/d) were administered simultaneously beginning on cycle day 3. Ovulation was cotriggered by a gonadotropinreleasing hormone (GnRH) agonist (0.1 mg) and hCG (1000IU) when dominant follicles matured. A short protocol was used as a control. The primary end-point was the ongoing pregnancy rate per transfer and incidence of OHSS. Doses of hMG administrated in group A are significantly higher than those in the controls. LH suppression persisted during ovarian stimulation and no incidence of premature LH surge was seen in both groups. The fertilization rate and the ongoing pregnant rate in the study group were higher than that in the control. The number of oocytes retrieved, mature oocytes, clinical pregnancy rates per transfer, implantation rates, and cumulative pregnancy rates per patient were comparable between the 2 groups. The incidence of OHSS was low between the 2 groups, with no significant difference. The study showed that MPA has the advantages of an oral administration route, easy access, more control over LH levels. A possible reduction in the incidence of moderate or severe OHSS with the MPA protocol should be viewed with caution as the data is small. Large randomized trials with adequate sample size remain necessary.